Comprehensive Genotypic Characterization of Antiseptic Resistance Determinants in Pseudomonas aeruginosa Clinical Isolates - Sulaiman A. Abdullah; Ban H. Khalaf; Nabaa Q. Jameel (The Open Biotechnology Journal, 2026)
Introduction The growing application of biosides post-COVID-19 has heightened concern over the development and spread of antiseptic resistance determinants, especially qac genes in different types of bacteria. This study aimed to evaluate antiseptic resistance determinants in clinical P. aeruginosa isolates and to determine their response to antimicrobial resistance and biofilm-forming ability. Methods Fifty clinical P. aeruginosa isolates were evaluated for antimicrobial susceptibility using the Kirby-Bauer disk diffusion method, Biofilm formation using the microtiter plate crystal violet assay, and biocide tolerance by broth microdilution. PCR was performed to identify qacE and qacEΔ1 genes in selected highly resistant isolates. Statistical analysis was applied to identify the correlation among variables. Results The findings showed a high rate of MDR (64.0%) and XDR (6.0%). Biofilm assays showed strong (38.0%), moderate (30.0%), and weak (30.0%) production. Furthermore, strong /moderate biofilm formation was significantly associated with MDR/XDR phenotypes ( p < 0.0001 ). Reduced antiseptic sensitivity was detected in (60.0%) of isolates and strongly correlated with both antimicrobial resistance status and biofilm strength ( p < 0.0001 ). Molecular profiling of selected resistance isolates showed a universal presence of the qacEΔ1 gene (100%) and high prevalence of the qacE gene (73.3%). Discussion The significant correlation between qac genes and strong biofilm ability demonstrates a key mechanism of antibiotic and biocide tolerance in P. aeruginosa. Conclusion Qac genes are highly prevalent in clinical P. aeruginosa isolates and strongly correlated with multidrug resistance and biofilm-forming ability. Ongoing molecular monitoring of the biocide resistance genes in clinical setups is vital to prevent the propagation of exceptionally stubborn strains in clinical environments.